Talking over the years : a handbook of dynamic psychotherapy with older adults - Evans, Sandra (NHS psychiatrist); Garner, Jane, FRCPsych (Brunner-Routledge, 2004)
Drawing on a wealth of clinical material Talking Over the Years increases psychodynamic awareness helping professionals become more sensitive to their patient's needs and informing psychiatric work with older people.